Inner-city poverty in the United States - Lynn, Laurence E., 1937-; McGeary, Michael G. H. (National Academy Press, 1990)
Documents the growth of concentrated poverty in central cities of the United States and examines what is known about its causes and effects. This volume is useful for policymakers, program administrators, researchers studying urban poverty issues, faculty, and students.